OUTILS ET NOTIONS D’URBANISATION EN MILIEU RURAL - BENABBAS, M.; DJAGHROURI, D. (Courrier du Savoir, 2017)
The term "urbanism" is a recent creation, it appeared in the French language in the 1910s to designate a new field of multidisciplinary actions, born from the specific demands of industrial society, developing a thought and method of thinking about the city, urbanism presents itself as the science of spatial organization and has a dual facets, the theoretical and the applied one and also, endowed with means and tools of urbanism. Typical features of modern town planning are general town planning plans, which summarize land use objectives and limits, zoning and subdivision controls that specify permitted land use, densities, requirements for streets, utilities and other facilities. Although urbanization is related to the city, nowadays, this phenomenon extends to take into account the rural space, we speak of rurbanisation, this often happens by the development of the habitat around a nucleus of the former village. This development is carried out either in an anarchic way due to individual initiative (known as "sprawl" of space) or more rationally when new constructions are carried out by real estate developers who offer residential subdivisions and Facilities equivalent to those of cities.